Luhmann without society - Leon Wansleben (Finance and Society, 2018)
Konings successfully mobilizes social theory to demonstrate how various post-Marxist, Polanyian, and Foucauldian analyses fail to make sense of financialization and neoliberal governance as persistent societal formations. In their place he offers an analysis focused on the logic of 'leverage', which he sees as a source of not only private gain but also governmental power. I fully endorse Konings' turn to social theory, and in particular to the work of Niklas Luhmann. But I suggest that, since Konings leaves out Luhmann's broader theory of society, he can neither capture the tight couplings between the economy and politics presupposed in neoliberal governance, nor contextualize this governance as a 'provincial', US-centred project.
Keywords: 300